Radio-over-fiber for increasing effective coverage of motorway access networks. (6th January 2009) - Xing, Weixi; Li, Yue; Nguyen, Xuan Huan; Zheng, Jun
This paper proposes a radio-over-fiber (RoF) system architecture for a motorway access network to provide broadband communication for high-speed vehicles. The proposed system architecture employs a star-tree topology with a central control system connected to the fixed-line data collection parts on one side and the wireless access points (APs) on the other side to transmit data information from/to road vehicles. To address the coverage problem, a motor-picocell scheme (MPS) is proposed, which converts a conventional base station (BS) into a number of picocells and deploy the picocells along a motorway based on the combination of RoF and TDMA technologies. To improve the performance of the proposed system architecture, a cross-layer design is also proposed based on joint adaptive modulation (AM) and buffer management. In the cross-layer design, the AM scheme adapted to the channel quality can result in different transmission rate at the transmitter side and packet error rate at the receiver side, and the jointly-designed buffer management scheme with an optimal threshold can achieve the best utilisation of the network.